An unusual complication after placement of an inferior vena cava filter via right internal jugular vein access. Issue 1 (January 2019) - Nas, Hala; Bowe, Dedrick; Soubani, Ayman O
Introduction: Totally implantable venous access devices are used extensively worldwide in cancer patients for administration of venotoxic agents, blood sampling, and nutrition. Their tip is usually positioned at the junction of superior vena cava and right atrium. Inferior vena cava filters are usually used for deep venous thrombosis in cases where anticoagulation is contraindicated; they can be inserted either via internal jugular or femoral access depending on patient conditions and preference. Case description: We are describing here a case of totally implantable venous access device fracture following a right internal jugular approach for inferior vena cava filter placement as the patient had inferior vena cava thrombus below the renal veins, extending into the right common iliac vein prohibiting femoral approach. Conclusion: Iatrogenic fracture of totally implantable venous access device is a potential complication of accessing the internal jugular vein for other procedures such as insertion of inferior vena cava filter.